Особенности применения мерчендайзинга товаров бытовой техники (Путеводитель предпринимателя, 2020)
In the article it is shown the present merchandising state in the household appliances shops in Novosibirsk. Basic merchandising elements and factors influencing their efficiency are appraised. Peculiarities of the merchandising use in different retail mercantile businesses of the household appliances are exposed.